A high-tolerance locking nut and preparation method thereof
By using metal raw materials with specific ratios and fine process treatment, a strong resistance lock nut is made, which solves the problems of nut corrosion and brittle fracture in high temperature and acid-base environments, and achieves excellent corrosion resistance and mechanical properties.
Patent Information
- Application Number
- CN202310512859.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-05-09
AI Technical Summary
Existing bolts and nuts are prone to corrosion and brittle fracture in high temperature and acid-base environments, and lack strong tolerance.
A strong tolerance lock nut is made of raw materials with specific ratios (C, Cu, Cr, P, Mo, Ni, V, W, Ti, Nb, Ga, B), and is smelted, cast, and fired through high temperature. Tempering and finishing processes to form excellent corrosion resistance and mechanical properties.
It significantly improves the high temperature, corrosion and mechanical properties of the nut and extends its service life.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of functional fasteners, and more specifically, to a high-tolerance locking nut and a preparation method thereof. Background Art
[0002] Bolts and nuts are a relatively large number of fasteners, which mainly play the role of connection, positioning and sealing in mechanical components. With the continuous large-scale development of various types of machinery, equipment and construction projects, the working conditions of bolts and nuts have become more severe, so the performance requirements for bolts and nuts are also relatively higher.
[0003] For example, when some materials containing acid and alkali are subjected to high temperature treatment, in order to improve the efficiency of material transfer, the materials are usually placed on a bracket. - NH4 + 、SO4 2- Plasma will gradually precipitate and adhere to the surface of the bolts and nuts on the bracket. Coupled with the effects of high temperature and high humidity, the bolts and nuts are likely to corrode and break.
[0004] At present, people usually paint or electroplate oxidation-resistant metal on the surface of bolts and nuts, but this protection is only an outer film. Once the protective layer is damaged, the main body of the bolt and nut will easily rust. In addition, under the long-term action of high temperature, bolts and nuts are also prone to brittle fracture. Therefore, there is an urgent need for a locking bolt and nut that has strong tolerance to high temperature and acid and alkali substances. Summary of the invention
[0005] In order to overcome the defect that the locking nut has poor tolerance to high temperature and acid and alkali substances, the present application provides a high-tolerance locking nut and a preparation method thereof.
[0006] In a first aspect, the present application provides a high-tolerance locking nut, which adopts the following technical solution:
[0007] A high-tolerance locking nut is made of the following raw materials in weight percentage: C: 0.35-0.40%; Cu: 0.3-0.5%; Cr: 0.7-1.3%; P: 0.007-0.012%; Mo: 0.10-0.20%; Ni: 1.0-1.4%; V: 0.08-0.14%; W: 0.6-0.8%; auxiliary additives: 0.42-0.75%; the rest is Fe and unavoidable impurities.
[0008] Cr and Cu are both alloying elements with extremely effective corrosion resistance in alloy steels. Among them, Cr can automatically fill the gaps formed by pitting corrosion of the material, form a dense protective layer, prevent pitting corrosion from developing in depth, effectively improve the material's oxidation resistance and corrosion resistance, and at the same time improve the material's permeability to enhance its strength. Cu can refine the material's grains, increase the material's self-corrosion potential, and thus reduce the material's corrosion rate. When Cr, Cu, and P are used at the same time, Cu can also increase Cr's passivation properties on alloy materials, and P can be used as a degasser to further improve the material's corrosion resistance. However, the addition of P will also significantly reduce the material's delayed fracture resistance.
[0009] When Mo and V are mixed, Mo and V carbides will undergo a secondary hardening effect, thereby further refining the grain size of the material and increasing its notch tensile critical stress, while improving the material's delayed fracture resistance. When Ni is added, in addition to enhancing the mechanical properties of the material itself, Ni can also cooperate with Mo and V to further increase the material's delayed fracture resistance.
[0010] When W and V are mixed, W, V and C will form WC and VC carbides with high melting point and high stability, which will make the material have excellent strength and toughness even in high temperature environment. In addition, W diffuses slowly in the material matrix, so it is partially discharged from the new phase during the tempering process and gathers at the interface front to control the growth of particles. V forms VC, which precipitates during the tempering process to form a dispersed phase, promoting the generation of secondary hardening, while W promotes the dispersion hardening effect of V.
[0011] Preferably, the auxiliary additive includes Ti.
[0012] Cu can improve the strength and toughness of the material, but it is easy to produce hot brittleness during hot working. When Cu is added together with Ti, Cu and Ti will form compounds such as Ti2Cu3, TiCu and Ti2Cu. The above compounds have a high crystallization point and can be used as non-spontaneous nucleation, thereby refining the structure and grains, effectively reducing the possibility of hot brittleness during hot working of the material.
[0013] Preferably, the auxiliary additive further includes Nb.
[0014] When Ti and Nb are added at the same time, Ti, Nb, C, and N will generate carbonitride particles to refine the austenite grains, thereby forming hydrogen traps, improving the strength and toughness of the material, and enhancing the delayed fracture resistance of the material. At the same time, Ti and Nb can also cooperate with Ni to further improve the mechanical properties of the material.
[0015] Preferably, the auxiliary additive also includes Ga.
[0016] When Ga and Ti are mixed, Ga and Ti will form a peritectic binary state, thereby improving the fluidity of Ti, which is beneficial to the mixing of various elements in the material and further improving the tolerance of the material.
[0017] Preferably, the auxiliary additive also includes B.
[0018] When Ti and B are mixed, the material will obtain better grain boundary strength, effectively reducing the possibility of cracks occurring along the grain boundary, thereby improving the material's endurance strength, reducing the material's sensitivity to high-temperature endurance notches, and greatly improving the material's creep fracture toughness. At the same time, B can also generate CrB reinforcement phase with Cr, thereby improving the rare earth layer's structural strength while improving the bonding strength between the heavy rare earth layer and the material body.
[0019] Preferably, the high-tolerance locking nut is made of the following raw materials in weight percentage: C: 0.35-0.40%; Cu: 0.3-0.5%; Cr: 0.7-1.3%; P: 0.007-0.012%; Mo: 0.10-0.20%; Ni: 1.0-1.4%; V: 0.08-0.14%; W: 0.6-0.8%; Ti: 0.2-0.4%; Nb: 0.10-0.14%; Ga; 0.06-0.09%; B: 0.08-0.12%; the rest is Fe and unavoidable impurities.
[0020] When the high-tolerance locking nut adopts the raw materials in the above weight percentage, the high-tolerance locking nut has better high-temperature resistance, corrosion resistance and excellent mechanical properties.
[0021] In a second aspect, the present application provides a method for preparing a high-tolerance locking nut, using the following technical solution:
[0022] A method for preparing a high-tolerance locking nut comprises the following steps:
[0023] Smelting: C, Cu, Cr, P, Mo, Ni, V, W, auxiliary additives and iron are mixed according to the above weight percentages, and then smelted and refined at high temperature to obtain refined molten steel;
[0024] Casting: Pour the refined molten steel into the mold for casting at a casting temperature of 1500-1600°C, and slowly cool to obtain a casting body;
[0025] Normalizing and tempering: keep the casting body at 1000-1200℃ for 3-5h, then slowly cool it; then keep it at 700-800℃ for 3-5h to obtain the crude nut;
[0026] Finishing: The rough nut is finished to the specified size, and then the surface is heat treated at a temperature of 500-600℃, and then kept at 400-500℃ for 3-4h to finally obtain a strong-tolerance locking nut.
[0027] A method for preparing a high-tolerance locking nut comprises the following steps:
[0028] Pretreatment: Mix part of Cu with part of B, Cr and P, then melt and cool to obtain a first solid solution; Mix C with Mo, V, Ni and W, then melt and cool to obtain a second solid solution; Mix the remaining Cu and the remaining B with Ti, Nb and Ga, then melt and cool to obtain a third solid solution;
[0029] Melting: Mix the remaining C with the first solid solution, the second solid solution, the third solid solution and iron, and then melt and refine at high temperature to obtain refined molten steel;
[0030] Casting: Pour the refined molten steel into the mold for casting at a casting temperature of 1500-1600°C, and slowly cool to obtain a casting body;
[0031] Normalizing and tempering: keep the casting body at 1000-1200℃ for 3-5h, then slowly cool it; then keep it at 700-800℃ for 3-5h to obtain the crude nut;
[0032] Finishing: The rough nut is finished to the specified size, and then the surface is heat treated at a temperature of 500-600℃, and then kept at 400-500℃ for 3-4h to finally obtain a strong-tolerance locking nut.
[0033] Compared with directly melting C, Cu, Cr, P, Mo, Ni, V, W, Ti, Nb, Ga and B, the method of melting and cooling part of Cu and part of B, Cr and P to obtain a first solid solution can enable Cu, B, Cr and P to form a composite system in advance, thereby further improving the corrosion resistance and delayed fracture resistance of the high-tolerance locking nut.
[0034] The method of mixing C with Mo, V, Ni, and W to obtain a second solid solution by melting and cooling can promote the pre-formation of a composite system of C, Mo, V, Ni, and W, and further improve the mechanical properties, delayed fracture resistance, and high temperature resistance of the high-tolerance locking nut.
[0035] The method of melting and cooling Cu, B, Ti, Nb, and Ga to obtain a third solid solution can promote the pre-formation of a composite system of Cu, B, Ti, Nb, and Ga, and further improve the creep fracture toughness and high temperature resistance of the high-tolerance locking nut.
[0036] Preferably, in the first solid solution, the mass ratio of Cu, B, Cr and P is 0.2:0.05:1.0:0.01; in the second solid solution, the mass ratio of C, Mo, V, Ni and W is 0.38:0.15:0.11:1.2:0.7; in the third solid solution, the mass ratio of Cu, B, Ti, Nb and Ga is 0.2:0.05:0.3:0.12:0.075.
[0037] When the raw materials of the first solid solution, the second solid solution and the third solid solution adopt the above weight ratio, the prepared high-tolerance locking nut has better high temperature resistance, corrosion resistance and mechanical properties.
[0038] In summary, this application has the following beneficial effects:
[0039] 1. When Cr, Cu and P are used at the same time, Cu can also increase the passivation performance of Cr on alloy materials, while P can be used as a degassing agent to further improve the corrosion resistance of the material. However, the addition of P will also significantly reduce the delayed fracture resistance of the material. B can also generate CrB reinforcing phase with Cr, thereby improving the structural strength of the rare earth layer and the bonding strength between the heavy rare earth layer and the material body.
[0040] 2. When Ni is added, in addition to enhancing the mechanical properties of the material itself, Ni can also be coordinated with Mo and V to further increase the delayed fracture resistance of the material. When W and V are mixed, W, V and C will form WC and VC carbides with high melting points and high stability, thus enabling the material to have excellent strength and toughness even in high temperature environments.
[0041] 3. When Cu and Ti are added together, Cu and Ti will form compounds such as Ti2Cu3, TiCu and Ti2Cu, thereby refining the structure and grains, effectively reducing the possibility of hot brittleness during the hot working of the material. Ti, Nb, C and N will generate carbonitride particles to refine the austenite grains, thereby forming hydrogen traps, improving the strength and toughness of the material, and enhancing the material's delayed fracture resistance.
[0042] When Ti and B are mixed, the material will obtain better grain boundary strength, effectively reducing the possibility of cracks occurring along grain boundaries, thereby improving the material's endurance strength, reducing the material's sensitivity to high-temperature endurance notches, and greatly improving the material's creep fracture toughness. DETAILED DESCRIPTION
[0043] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0044] raw material
[0045] C CAS: 7440-44-0; Cu CAS: 7440-50-8; Cr CAS: 7440-47-3; P CAS: 7723-14-0; MoCAS: 7439-98-7; Ni CAS: 7440-02-0; CAS: 7440-32-6; Nb CAS: 7440-3-1; Ga CAS: 7440-55-3; B CAS: 7440-42-8; Fe CAS: 7439-89-6.
[0046] Example
[0047] Example 1
[0048] A high-tolerance locking nut is made of the following raw materials in weight percentage: C: 0.38%; Cu: 0.4%; Cr: 1.0%; P: 0.01%; Mo: 0.15%; Ni: 1.2%; V: 0.11%; W: 0.7%; Ti: 0.3%; Nb: 0.12%; Ga: 0.075%; B: 0.1%; the rest is Fe and unavoidable impurities.
[0049] A method for preparing a high-tolerance locking nut comprises the following steps:
[0050] Melting: C, Cu, Cr, P, Mo, Ni, V, W, Ti, Nb, Ga, B and iron are mixed according to the above weight percentages, and then smelted and refined at high temperature in a nitrogen environment to obtain refined molten steel at a melting temperature of 2000°C;
[0051] Casting: Pour the refined molten steel into the mold for casting at a casting temperature of 1550°C (1500-1600°C is appropriate), followed by slow cooling at a rate of 200°C / h to obtain a casting body;
[0052] Normalizing and tempering: keep the casting body at 1100°C (1000-1200°C) for 4h (3-5h), then slowly cool it at a rate of 200°C / h, and then keep it at 750°C (700-800°C) for 4h (3-5h) to obtain a crude nut;
[0053] Finishing: The rough nut is finished to the specified size, and then the surface is heat treated at a temperature of 550℃ (500-600℃ is suitable), and then kept at 450℃ (400-500℃ is suitable) for 3.5h (3-4h is suitable), and finally a strong tolerance locking nut is obtained.
[0054] Example 2-3
[0055] The difference from Example 1 is that the weight percentage of the high-tolerance locking nut raw material is different, as shown in Table 1.
[0056] Table 1 Weight percentage of each raw material for medium-strength tolerance locking nut of Examples 1-3 (wt%)
[0057] Example 1 Example 2 Example 3 C 0.38 0.35 0.40 Cu 0.4 0.5 0.3 Cr 1.0 1.3 0.7 P 0.01 0.007 0.012 Mo 0.15 0.10 0.20 Ni 1.2 1.4 1.0 V 0.11 0.14 0.08 W 0.7 0.8 0.6 Ti 0.3 0.2 0.4 Nb 0.12 0.10 0.14 Ga 0.075 0.09 0.06 B 0.1 0.12 0.08 Fe margin margin margin
[0058] Example 4
[0059] The difference from Example 1 is that B is not added.
[0060] Example 5
[0061] The difference from Example 4 is that Ga is no longer added.
[0062] Example 6
[0063] The difference from Example 5 is that no Nb is added.
[0064] Example 7
[0065] The difference from Example 6 is that Ti is no longer added.
[0066] Example 8
[0067] The difference from Example 1 is that the raw materials are first pretreated before smelting;
[0068] Preprocessing:
[0069] Part of Cu is mixed with part of B, Cr and P, and then melted and cooled to obtain a first solid solution; wherein, in the first solid solution, the mass of Cu accounts for 0.2wt% of the strong tolerance locking nut; the mass of B accounts for 0.05wt% of the strong tolerance locking nut; the melting temperature is 2200°C;
[0070] C is mixed with Mo, V, Ni and W, and then melted and cooled to obtain a second solid solution; wherein the melting temperature is 1800°C;
[0071] The remaining Cu and the remaining B are mixed with Ti, Nb, and Ga, and then melted and cooled to obtain a third solid solution; wherein, in the third solid solution, the mass of Cu accounts for 0.2wt% of the high-tolerance locking nut; the mass of B accounts for 0.05wt% of the high-tolerance locking nut; the melting temperature is 2000°C.
[0072] Example 9
[0073] The difference from Example 8 is that in the first solid solution, the mass of Cu accounts for 0.1wt% of the strong tolerance locking nut; the mass of B accounts for 0.02wt% of the strong tolerance locking nut; in the third solid solution, the mass of Cu accounts for 0.3wt% of the strong tolerance locking nut; the mass of B accounts for 0.08wt% of the strong tolerance locking nut.
[0074] Example 10
[0075] The difference from Example 8 is that in the first solid solution, the mass of Cu accounts for 0.3wt% of the strong tolerance locking nut; the mass of B accounts for 0.08wt% of the strong tolerance locking nut; in the third solid solution, the mass of Cu accounts for 0.1wt% of the strong tolerance locking nut; the mass of B accounts for 0.02wt% of the strong tolerance locking nut.
[0076] Comparative Example
[0077] Comparative Example 1
[0078] A high-strength nut is made of the following raw materials in weight percentage: C 0.445%, Si 0.285%, Mn 1.06%, P 0.0193%, S 0.012%, Cr 0.996%, Mo 0.190%, Ni 0.207%, RE 0.019%, and the balance is iron and inevitable impurities.
[0079] A method for preparing a high-strength nut comprises the following steps:
[0080] Melting: C, Si, Mn, P, S, Cr, Mo, Ni, RE and iron are mixed according to the above weight percentages, and then smelted and refined at high temperature in a nitrogen environment to obtain refined molten steel at a melting temperature of 2000°C;
[0081] Casting: Pour the refined molten steel into the mold for casting at a casting temperature of 1550°C (1500-1600°C is appropriate), followed by slow cooling at a rate of 200°C / h to obtain a casting body;
[0082] Normalizing and tempering: keep the casting body at 1100°C (1000-1200°C) for 4h (3-5h), then slowly cool it at a rate of 200°C / h, and then keep it at 750°C (700-800°C) for 4h (3-5h) to obtain a crude nut;
[0083] Finishing: The rough nut is finished to the specified size, and then the surface is heat treated at 550℃ (500-600℃ is suitable), and then kept at 450℃ (400-500℃ is suitable) for 3.5h (3-4h is suitable), and finally a high-strength nut is obtained.
[0084] Comparative Example 2
[0085] The difference from Example 7 is that no Cu is added.
[0086] Comparative Example 3
[0087] The difference from Example 7 is that V is not added.
[0088] Comparative Example 4
[0089] The difference from Example 7 is that W is not added.
[0090] Performance testing
[0091] Detection Methods
[0092] 1. Corrosion resistance test
[0093] Six samples were taken from Examples 1-10 and Comparative Examples 1-4 respectively, and then three samples were taken and the tensile strength of the samples was tested according to ASTM E8M "Metallic Material Tensile Test Method" and the average value was taken to finally obtain the tensile strength before corrosion.
[0094] Afterwards, the other three samples were immersed in a mixed aqueous solution of sodium sulfate, sodium chloride and acetic acid for 168 hours, with the mass percentage of sodium sulfate being 5%, the mass percentage of sodium chloride being 10%, and the mass percentage of acetic acid being 20%. The immersed samples were then washed and dried, and finally the tensile strength of the samples was tested in accordance with ASTM E8M "Metallic Material Tensile Test Methods" and the average value was taken to obtain the post-corrosion tensile strength.
[0095] Finally, the corrosion resistance is calculated.
[0096] Corrosion resistance = tensile strength after corrosion / tensile strength before corrosion * 100%.
[0097] 2. High temperature resistance test
[0098] Six samples were taken from Examples 1-10 and Comparative Examples 1-4 respectively, and then three samples were taken and the tensile strength of the samples was tested according to ASTM E8M "Metallic Material Tensile Test Method" and the average value was taken to finally obtain the tensile strength before high temperature.
[0099] Afterwards, the other three samples were placed at a temperature of 500°C for 156 hours, followed by natural cooling, and finally the tensile strength of the samples was tested in accordance with ASTME8M "Metallic Material Tensile Test Method" and the average value was taken to obtain the tensile strength after high temperature.
[0100] Finally, the high temperature resistance strength is calculated.
[0101] High temperature resistance strength = tensile strength after high temperature / tensile strength before high temperature * 100%.
[0102] 3. Delayed fracture resistance test
[0103] Six samples were taken from Examples 1-10 and Comparative Examples 1-4, and then three samples were taken and directly subjected to a breaking load test, and then a non-breaking load of more than 100 hours before treatment was obtained. After that, the other three samples were immersed in a 15% by mass HCl aqueous solution for 30 minutes, and then washed and dried and then subjected to a breaking load test, and then a non-breaking load of more than 100 hours after treatment was obtained.
[0104] Finally, the delayed fracture strength was calculated.
[0105] Delayed fracture resistance = load without fracture for more than 100 hours after treatment / load without fracture for more than 100 hours before treatment * 100%.
[0106] The above performance test data are specifically shown in Table 2.
[0107] Table 2 Test data table of Examples 1-10 and Comparative Examples 1-4
[0108] Corrosion resistance High temperature strength Delayed fracture strength Example 1 94.4% 93.1% 91.6% Example 2 91.3% 91.5% 85.9% Example 3 91.9% 91.0% 86.4% Example 4 94.3% 90.1% 87.2% Example 5 93.7% 89.4% 86.6% Example 6 93.5% 88.3% 82.1% Example 7 92.3% 85.3% 78.9% Example 8 97.4% 97.6% 94.9% Example 9 96.9% 96.2% 93.4% Example 10 96.7% 96.4% 93.1% Comparative Example 1 85.2% 73.6% 64.4% Comparative Example 2 89.2% 85.1% 78.6% Comparative Example 3 93.1% 78.9% 71.3% Comparative Example 4 92.9% 80.0% 73.1%
[0109] Referring to Examples 1-3 and Comparative Example 1 and in combination with Table 2, it can be seen that, relative to Comparative Example 1, the corrosion resistance, high temperature resistance and delayed fracture resistance of Examples 1-3 are significantly improved, which indicates that the element composition in Examples 1-3 enables the prepared locking bolts and nuts to have better corrosion resistance, high temperature resistance and delayed fracture resistance.
[0110] Compared with Example 1, the corrosion resistance, high temperature resistance and delayed fracture strength of Examples 2-3 are slightly reduced, which shows that when the raw material components of the high-tolerance locking bolts and nuts adopt the weight percentage of Example 1, the high-tolerance locking bolts and nuts have better corrosion resistance, high temperature resistance and delayed fracture strength.
[0111] Referring to Example 1 and Examples 4-7 and in combination with Table 2, it can be seen that, relative to Example 1, the corrosion resistance of Example 4 is basically unchanged, but the high temperature resistance and delayed fracture resistance of Example 4 are significantly reduced, which shows that the addition of B is beneficial to improving the high temperature resistance and delayed fracture resistance of the high-tolerance locking bolts and nuts.
[0112] The reason is that when Ti and B are mixed, the material will obtain better grain boundary strength, effectively reducing the possibility of cracks occurring along the grain boundaries, thereby improving the material's endurance strength, reducing the material's sensitivity to high-temperature endurance notches, and greatly improving the material's creep fracture toughness.
[0113] Compared with Example 4, the corrosion resistance, high temperature resistance and delayed fracture strength of Example 5 are slightly reduced, which shows that the addition of Ga has an effect on the corrosion resistance, high temperature resistance and delayed fracture strength of the high-tolerance locking bolts and nuts.
[0114] The reason is that when Ga and Ti are mixed, Ga and Ti will form a peritectic binary state, which will increase the fluidity of Ti, and then be beneficial to the mixing of the various elements of the material, thereby affecting the performance improvement effect of the functional elements.
[0115] Compared with Example 5, the corrosion resistance of Example 6 is basically unchanged, the high temperature resistance of Example 6 is slightly reduced, and the delayed strength of Example 6 is significantly reduced, which shows that the addition of Nb can effectively improve the delayed fracture strength performance of high-tolerance locking bolts and nuts. The reason is that Ti, Nb, C, and N will generate carbonitride particles to refine austenite grains, thereby forming hydrogen traps, improving the strength and toughness of the material, and enhancing the delayed fracture resistance of the material.
[0116] Compared with Example 6, the corrosion resistance, high temperature resistance and delayed fracture resistance of Example 7 are significantly reduced, which shows that the addition of Ti has a certain influence on the corrosion resistance, high temperature resistance and delayed fracture resistance of high-tolerance bolts and nuts.
[0117] The reason is that Cu can improve the strength and toughness of the material, but it is easy to produce hot brittleness during hot working. When Cu and Ti are added together, Cu and Ti will form compounds such as Ti2Cu3, TiCu and Ti2Cu. The above compounds have a high crystallization point and can be used as non-spontaneous nucleation, thereby refining the structure and grains, effectively reducing the possibility of hot brittleness during hot working of the material. Moreover, Ti itself also has excellent corrosion resistance.
[0118] It can be seen from Example 1, Examples 8-10 and Table 2 that, relative to Example 1, the corrosion resistance, high temperature resistance and delayed fracture resistance of Examples 8-10 are significantly improved, which shows that the pretreatment operation can further improve the corrosion resistance, high temperature resistance and delayed fracture resistance of the high-tolerance locking bolts and nuts.
[0119] The reason is that the method of melting and cooling part of Cu and part of B, Cr and P to obtain the first solid solution can enable Cu, B, Cr and P to form a composite system in advance, thereby further improving the corrosion resistance and delayed fracture resistance of the high-tolerance locking nut.
[0120] The method of mixing C with Mo, V, Ni, and W to obtain a second solid solution by melting and cooling can promote the pre-formation of a composite system of C, Mo, V, Ni, and W, and further improve the mechanical properties, delayed fracture resistance, and high temperature resistance of the high-tolerance locking nut.
[0121] The method of melting and cooling Cu, B, Ti, Nb, and Ga to obtain a third solid solution can promote the pre-formation of a composite system of Cu, B, Ti, Nb, and Ga, and further improve the creep fracture toughness and high temperature resistance of the high-tolerance locking nut.
[0122] Compared with Example 8, the corrosion resistance, high temperature resistance and delayed fracture resistance of Examples 9-10 are relatively low. This shows that when the components of the first solid solution and the third solid solution adopt the mass ratio of Example 8, the high-tolerance locking bolts and nuts have better corrosion resistance, delayed fracture resistance and high temperature resistance.
[0123] With reference to Example 7, Comparative Examples 2-4 and in combination with Table 2, it can be seen that, relative to Example 7, the high temperature resistance and delayed fracture resistance of Comparative Example 2 are slightly reduced, but the corrosion resistance of Comparative Example 2 is significantly reduced.
[0124] The reason is that Cu can refine the grain size of the material, increase the self-corrosion potential of the material, and thus reduce the corrosion rate of the material. When Cr, Cu, and P are used at the same time, Cu can also increase the passivation performance of Cr on the alloy material, while P can act as a degassing agent to further improve the corrosion resistance of the material.
[0125] Compared with Example 7, the high temperature resistance of Comparative Examples 3-4 is basically unchanged, but the high temperature resistance and delayed fracture resistance of Comparative Example 3 are significantly reduced.
[0126] The reason is that when Mo and V are mixed, Mo and V carbides will undergo a secondary hardening effect, thereby further refining the grain size of the material and increasing its notch tensile critical stress, while improving the material's delayed fracture resistance. When Ni is added, in addition to enhancing the mechanical properties of the material itself, Ni can also cooperate with Mo and V to further increase the material's delayed fracture resistance.
[0127] When W and V are mixed, W, V and C will form WC and VC carbides with high melting point and high stability, which will make the material have excellent strength and toughness even in high temperature environment. In addition, W diffuses slowly in the material matrix, so it is partially discharged from the new phase during the tempering process and gathers at the interface front to control the growth of particles. V forms VC, which precipitates during the tempering process to form a dispersed phase, promoting the generation of secondary hardening, while W promotes the dispersion hardening effect of V.
[0128] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-tolerance locking nut, characterized in that: Made of the following raw materials in weight percentage: C: 0.35-0.40%; Cu: 0.3-0.5%; Cr: 0.7-1.3%; P:0.007-0.012%; Mo: 0.10-0.20%; Ni: 1.0-1.4%; V: 0.08-0.14%; W: 0.6-0.8%; Ti: 0.2-0.4%; Nb: 0.10-0.14%; Ga; 0.06-0.09%; B: 0.08-0.12%; the rest is Fe and inevitable impurities, and the Ti, Nb, Ga and B constitute auxiliary additives.
2. A method for preparing the high-tolerance locking nut according to claim 1, characterized in that: The following steps are involved: Smelting: C, Cu, Cr, P, Mo, Ni, V, W, auxiliary additives and iron are mixed according to the above weight percentages, and then smelted and refined at high temperature to obtain refined molten steel; Casting: Pour the refined molten steel into the mold for casting at a casting temperature of 1500-1600°C, and slowly cool to obtain a casting body; Normalizing and tempering: keep the casting body at 1000-1200℃ for 3-5h, then slowly cool it; then keep it at 700-800℃ for 3-5h to obtain the crude nut; Finishing: The rough nut is finished to the specified size, and then the surface is heat treated at a temperature of 500-600℃, and then kept at 400-500℃ for 3-4h to finally obtain a strong-tolerance locking nut.
3. A method for preparing the high-tolerance locking nut according to claim 2, characterized in that: The following steps are involved: Pretreatment: Mix part of Cu with part of B, Cr and P, then melt and cool to obtain a first solid solution; Mix C with Mo, V, Ni and W, then melt and cool to obtain a second solid solution; Mix the remaining Cu and the remaining B with Ti, Nb and Ga, then melt and cool to obtain a third solid solution; Melting: Mix the remaining C with the first solid solution, the second solid solution, the third solid solution and iron, and then melt and refine at high temperature to obtain refined molten steel; Casting: Pour the refined molten steel into the mold for casting at a casting temperature of 1500-1600°C, and slowly cool to obtain a casting body; Normalizing and tempering: keep the casting body at 1000-1200℃ for 3-5h, then slowly cool it; then keep it at 700-800℃ for 3-5h to obtain the crude nut; Finishing: The rough nut is finished to the specified size, and then the surface is heat treated at a temperature of 500-600℃, and then kept at 400-500℃ for 3-4h to finally obtain a strong-tolerance locking nut.
4. The method for preparing a high-tolerance locking nut according to claim 3, characterized in that: In the first solid solution, the mass ratio of Cu, B, Cr and P is 0.2:0.05:1.0:0.01; in the second solid solution, the mass ratio of C, Mo, V, Ni and W is 0.38:0.15:0.11:1.2:0.7; in the third solid solution, the mass ratio of Cu, B, Ti, Nb and Ga is 0.2:0.05:0.3:0.12:0.075.
Citation Information
Patent Citations
High-strength steel excellent in delayed fracture resistance characteristics and metal bolts
CN101243197A
Industrial stable high-performance bolt steel and manufacturing method thereof
CN105002427A